The impact of physical activity on social anxiety among college students: the chain mediating effect of social support and psychological capital - Deng, Yiran; Wang, Xianliang (Frontiers in Psychology, 2024)
Objective As a topic of widespread concern in the fields of mental health and public health, social anxiety has many negative impacts on the physical and mental health of contemporary college students. Therefore, this study aims to provide new ideas for solving the problem of social anxiety among college students by exploring the potential mediating role of social support and psychological capital in the relationship between physical activity and social anxiety. Methods A cross-sectional survey was conducted on 874 college students from five universities in Shandong Province. Various self-report tools such as physical activity rating scale, social support scale, positive psychological capital scale, and social anxiety scale were used to collect information needed for this study. Related data. Use this to conduct descriptive statistical analysis, correlation analysis, and mediation effect analysis. Results The results showed that physical activity was significantly positively correlated with college students’ social support (r = 0.354, p < 0.01) and psychological capital (r = 0.448, p < 0.01), and social support was significantly positively correlated with psychological capital (r = 0.556, p < 0.01), the above three are significantly negatively correlated with social anxiety (r = −0.326, −0.381, −0.432, p < 0.01); the mediation effect analysis shows that physical activity has a significant direct effect on college students’ social anxiety The effect value is −0.136, accounting for 43.31% of the total effect; social support and psychological capital both play a separate mediating role between physical activity and social anxiety among college students, with effect values of −0.064 and −0.073 respectively, accounting for the total effect. 20.38, 23.25%, and also played a chain intermediary role, with an effect value of −0.041, accounting for 13.05% of the total effect. Conclusion Current research shows that physical activity can not only directly reduce social anxiety among college students, but also indirectly alleviate social anxiety among college students by increasing the level of social support and psychological capital. This has important reference significance for helping college students in China and even around the world overcome social anxiety.